Optimization of gradual hemolysis for isolation of hemoglobin from bovine erythrocytes - Pravilović Radoslava (Hemijska Industrija, 2012)
In this work, we describe an optimized procedure based on gradual hemolysis for the isolation of hemoglobin derived from bovine slaughterhouse erythrocytes in a membrane bioreactor. The membrane bioreactor system provided high yields of hemoglobin (mainly oxyhemoglobin derivate) and its separation from the empty erythrocyte membranes (ghosts). Ten different concentrations of hypotonic media were assessed from the aspect of the extent of hemolysis, hematocrit values of the erythrocyte suspensions, cell swelling and membrane deformations induced by decreased salt concentration. Effective gradual osmotic hemolysis with an extent of hemolysis of 83% was performed using 35 mM Na-phosphate/NaCl buffer of pH 7.2-7.4. Under these conditions most of the cell membranes presented the appearance of the normal ghosts under phase contrast microscope. The results show that isolation process yielded predominantly to oxyhemoglobin. Kinetic studies showed that maximal concentration of hemoglobin was reached after 40 min, but the process cycle at which recovery of 83% was achieved lasted for 90 min.